2009
DOI: 10.1021/jp907439c
|View full text |Cite
|
Sign up to set email alerts
|

Active Alloying of Au with Pt in Nanoclusters Supported on a Thin Film of Al2O3/NiAl(100)

Abstract: Self-organized alloying of Au with Pt in nanoclusters on a thin film of Al 2 O 3 /NiAl(100) is active at 300 K, toward a preferred bimetallic structure. The photoelectron spectra of Au nanoclusters (diameter 1.0-3.0 nm and height 0.2-1.0 nm) formed from vapor deposition on thin-film Al 2 O 3 /NiAl(100) show that the binding energy (BE) of Au 4f 7/2 decreases from 85.3 ( 0.1 eV upon incorporating subsequently deposited Pt, and saturates near 84.3 ( 0.1 eV with increasing Pt deposition; the line width decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 53 publications
(126 reference statements)
2
32
2
Order By: Relevance
“…Surprisingly, high resolution XPS investigations of PtAu bimetallic clusters on Al 2 O 3 thin films supported on NiAl(100) [73] reported results different from our Pt-Au clusters on TiO 2 (110). Specifically, there was a large shift in Au(4f) binding energy to lower values after the deposition of Pt.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Surprisingly, high resolution XPS investigations of PtAu bimetallic clusters on Al 2 O 3 thin films supported on NiAl(100) [73] reported results different from our Pt-Au clusters on TiO 2 (110). Specifically, there was a large shift in Au(4f) binding energy to lower values after the deposition of Pt.…”
Section: Discussioncontrasting
confidence: 97%
“…The reported absence of Au at the surface of the Pt-Au/ Al 2 O 3 clusters [73] is also in contrast to the Pt core-Au shell structures observed on the TiO 2 support observed here, as well as in other investigations of Pt-Au clusters. From DFT calculations, it was concluded that Pt-Au/Al 2 O 3 clusters consisted of Au core-Pt shell or Pt-Au intermixed structures with Au atoms residing inside the cluster [73].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Additionally, the surface composition of atomic Pt/Au ratio and the preparation method are significantly related to the electrocatalytic activity of bimetallic PtAu catalyst for FA oxidation reaction [13,[34][35][36]. In general, the high electrocatalytic activity of bimetallic PtAu catalyst has been ascribed to the special electronic effect [29,36,37], ensemble effect [11,20,30], and synergistic effect [34,38,39]. Many research findings have revealed that both Pt-onAu and PtAu alloy catalysts exhibited high electrocatalytic activity toward FA oxidation with much less CO ads than that on Pt catalyst surface.…”
Section: Introductionmentioning
confidence: 99%